"Мустанг-иноходец" и другие рассказы - Сетон-Томпсон Эрнест (Школьная библиотека, 2013)
Экземпляры: Д. О. (20210702) / Инвентарный номер: 45607 / Цена: 120.00 / Сис.шифр: 84(7Кан) / Авт.знак: С 33 / ГРНТИ: 17.82 / ББК: 84(7Кан)-44я43